On connection of modern geodynamic processes in carbonate rocks with tectonic activization of Petrivs’k-Kreminna fault - Сухов, Валерій Васильович; Суярко, Василь Григорович; Чуєнко, Олександр Володимирович (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
The given paper considers the connection of modern geodynamic processes in carbonate rocks with the tectonic activation of Petrivs’k-Kreminna fault. It is emphasized that faults in the region are the channels of the upward heat and mass transfer. The unloading of deep formation waters and endogenous fluids in the area Petrivs’k-Kreminna and other faults results from heat and mass transfer, which is brought about by the motions of lithospheric blocks of Donets’k folded structure. The present tense dynamic state of the geological system manifests itself in the constant uplifting of the hanging wings of Svyatohirs’k brachyanticline at a speed of 1,3-2,5 mm a year. Earthquakes with the focal depth of 10 km are associated with periodic geodynamic stress relaxation in the Archean-Proterozoic basement complex in the ancient geologically closed submeridional fault that intersects within Svyatohirs’k structure with the Petrivs’k-Kreminna fault. The modern and most recent tectonic activation of the latter is evidenced in the formation of hypogenic hydrogeochemical anomalies, accompanied by hydrochemical inversion. The groundwater here exhibit alkaline reaction (pH up to 8,2), an increased temperature (19- 27 °C) in the range of 0-300 m and a high content of hypogenic trace elements, among which carbon dioxide takes pride of place. The presence of CO2 increases the aggressiveness of underground water towards carbonate rocks, resulting in a chemical geodynamic process referred to as karst. Furthermore, abnormal physical and chemical properties of groundwater bring about suffusion processes in loamy, chalk strata of rocks. These geodynamic processes are associated with geological risks for buildings of Svyatohirs’k monastery. The study found that: 1) the tectonic activation of the Petrivs’k-Kreminna fault in various and, above all, the modern and contemporary periods of Alpine tectonogenesis is the dominant energy basis of geodynamic processes, including seismic activity; 2) carbon dioxide as atmospheric and deep genesis present in the groundwater of different types, is the major factor in the development of carbonate karst in Svyatohirs’k brachyanticline; 3) the isotopic analysis of δ13C and δ18O in aragonite chalk powder clearly showed that recrystallization of chalk into aragonite occurred involving deep formation waters saturated with endogenous (metamorphogenic or mantle) CO2.